Trends and determinants of nurses’ mental health following the COVID-19 pandemic in China: a longitudinal, comparative study over a two-year period - Liu, Yan; Lin, Yifei; Cui, Wenyao; Gu, Xianlin; Long, Youlin; Liu, Wenjie; Liao, Ga; Du, Liang; Huang, Jin (Frontiers in Psychiatry, 2024)
The COVID-19 pandemic has placed nurses at the forefront of healthcare, exposing them to various mental health challenges such as depression, anxiety, and post-traumatic stress disorder (PTSD). However the long-term effects and risk factors of the COVID-19 pandemic on nurses' mental health are unknown. The objective of our study is to investigate the enduring impact of the COVID-19 pandemic on the psychological distress and PTSD of nurses, while also identifying the factors that influence these outcomes.To investigate this question, we conducted a self-reported questionnaire survey of 8785 registered nurses recruited using snowball sampling methodology from 22 provinces in China, at five time points (T0-T4). At all times, we took measures of general health, while at the last four times we also measured PTSD. And we used logistic regression analysis to explore their impacts.The incidence of whole levels psychological distress among nurses was 27.7% at T0, peaking at 57.6% at T4. For severe psychological distress, it began at 5.5% at T0 and rose to 9.5% at T4. PTSD rates among nurses were recorded at 7.8% in T1, reaching a maximum of 14.7% in T4. They all got progressively worse in the volatility. In all times, coping strategies are independent factors for various levels of psychological distress and PTSD, while social support is a key factor for severe psychological distress and PTSD.Our findings indicated a gradual deterioration in the mental health of nurses following the COVID-19 outbreak. In all instances, coping strategies exhibit an independent correlation with all grades of psychological distress and posttraumatic stress disorder (PTSD), whereas social support emerges as an independent protective factor mitigating the risk of severe psychological distress and PTSD.